Internet addiction, behavioural aspects, and health related problems associated with it: a cross sectional study among engineering students of Jabalpur district - Thakur, Aditya; Peepre, Kunal; Vaswani, Anshi; Gupta, Khyati; Verma, Aman; Singh, Dhananjay; Kasar, Pradeep (International Journal of Research in Medical Sciences, 2017)
Background: With the rise of new generation gadgets, the risk of “internet addiction” is emerging as a significant behavioral addiction pandemic to be tackled worldwide. Internet addiction can be defined as an impulse disorder. Objective of the study was to determines the level of Internet addiction in Students. To identify the behavioural and any health-related problems associated with internet addiction among students. Methods: This study was a cross sectional study carried out in 7 different engineering colleges of Jabalpur city during the period of 1st July 2016 to 30th September 2016. Results: In present study the prevalence of internet addiction was found to be 74 %. 26 % of the participants were found with no internet addictions whereas 55 % and 17.67 % of the participants were found to be mild and moderate addicted whereas only 1.33 % of the participants were severely addicted to internet addiction. Participant who has internet addiction has 84.8 % of yelling and annoying behavior while 86.5 % participants with internet addiction have secretive and defensive behavior. Association was found to be highly significant (p = <0.001). Ill effects like problem related to eye have significant effect on the participants with internet addiction i.e. 66.17 %. Association of problem related to eye problems with internet addiction was significant with the p = 0.02. Conclusions: The problem is alarming and progressing to an addictive state in the near future Interventions like setting boundaries and detecting early warning signs of underlying psychopathology at the earliest are required